Fire as a driver of pyro-thermal niche variation in Acacia - McInnes, Sarah J.; Tangney, Ryan; Chong, Kelvin G. J.; Allen, Natalie E.; Ooi, Mark K. J. (Frontiers in Ecology and Evolution, 2025)
IntroductionMany plant species have evolved to persist in fire-prone regions under specific fire regimes. Seeds have developed mechanisms, including the breaking of physical seed dormancy by fire-related heat shock, that synchronize germination and seedling emergence with post-fire conditions conducive to successful recruitment. Seeds with physical dormancy can have their dormancy released by high soil temperatures during fire, with documented thermal thresholds varying widely from 60°C to 150°C. Generally, these thresholds are believed to be highly phylogenetically conserved, but how ecosystems shape seed thermal thresholds within widespread, geographically diverse genera is unknown. In this study, we sought to understand how soil heating under different fire regimes, seed traits, and climate variables all shape pyro-thermal niche metrics, dormancy-break, and mortality of Acacia seeds.MethodsUsing 35 Acacia species from across 12 vegetation types in Australia, we explored the relationship between seed pyro-thermal niche characteristics and fire return interval (FRI), fuel type (as a proxy for soil heating), mean annual temperature, and total annual precipitation.ResultsPyro-thermal niche metrics showed a hump-shaped relationship with both the minimum recommended FRI and fuel type, highlighting the role fire plays in shaping seed thermal thresholds. Climate variables showed no discernible relationship with pyro-thermal niche metrics.DiscussionThese results suggest that the mechanisms that shape the distribution of different seed dormancy classes are different from those that shape variation in pyro-thermal niche metrics. Understanding the processes driving plant population dynamics in fire-prone regions is essential for ecological understanding under a changing climate.